Study on Anti-Inflammatory Effect and Major Anti-Inflammatory Components of PSORI-CM02 by Zebrafish Model. (28th May 2020) - Yuan, Xiaohong; Huang, Leyu; Lei, Jiaqi; Long, Yingxin; Li, Cong
Abstract : PSORI-CM02 is an optimization formula of PSORI-CM01, which is a clinical herbal formula for the treatment for psoriasis in the Guangdong Provincial Hospital of Chinese Medicine. Previous research indicates that it plays a critical role in anti-inflammation and immunoregulation. Rhizoma smilacis glabrae (RSG) is one herbal medicine of PSORI-CM02, whose effective anti-inflammatory component is astilbin. This study aims to test the anti-inflammatory and immunoregulation effects of astilbin as well as RSG in PSORI-CM02, and we, respectively, used the CuSO4 -induced neutrophil-specific transgenic zebrafish model Tg(mpx: EGFP) and the melanin allele mutated Albino strain zebrafish model to visualize the effects of neutrophil recruitment and macrophage phagocytosis. Our data indicated that both PSORI-CM02 and astilbin had anti-inflammatory effects, leading to a reduction in the recruitment of neutrophils and promotion in macrophage phagocytosis. Nevertheless, the negative liquor of Rhizoma smilacis glabrae (PSORI-CM02 without RSG) also had anti-inflammatory and promoting macrophage phagocytosis effects. The results revealed the formula excluding RSG also had anti-inflammatory and immunoregulation effects, which demonstrated that RSG was not the major anti-inflammatory herbal medicine in PSORI-CM02. Similarly, astilbin was not the major anti-inflammatory active ingredient in the formula. The anti-inflammatory and the promotion of macrophage phagocytosis effect of PSORI-CM02 in vivo zebrafish were the results of multiple component interaction, which was the common characteristic of the Chinese medicine compound.